Wspieranie aktywności podmiotów gospodarki turystycznej przez samorząd lokalny na przykładzie wybranych gmin turystycznych województwa dolnośląskiego - Rapacz, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Enhancing entrepreneurial activities in economy (also tourist economy) is and should be animportant task for local authorities (especially at the level of communes). Such entrepreneurial projectsdepend, to a great extend, on willingness and skills in the application of instruments that localauthorities have at their disposal. These are both revenue and expenditure instruments, and alsoorganizational, administrative-legal as well as informational-promotional ones, which if adequatelyapplied may facilitate taking up economic activities or enhance their expansion. The article presentsbasic instruments that stimulate entrepreneurial activities in the economy of selected tourist communesin the area of Lower Silesia region. Additionally, an attempt to evaluate their practical applicationwas performed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 46-56